Mapping the Landscape: A Bibliometric Analysis of Employee Voice Research - Rifa Rahmadiah; Eeng Ahman; Budi Santoso; Yana Setiawan (Journal of Science and Education (JSE), 2025)
This study aims to systematically map the literature on "employee voice" through a bibliometric analysis. Research data were collected from 1,157 articles in the Scopus database, focusing on publications between 1982 and 2024. Using VOSviewer software, the study identifies intellectual structures, key themes, and emerging research trends. Findings show a significant growth in publications, with the United States, China, and the United Kingdom leading in contributions. Key journals such as the International Journal of Human Resource Management and Frontiers in Psychology are pivotal in shaping the field. Dominant themes include employee voice behavior, leader-member exchange, workplace conditions, and the growing role of digitalization, particularly post-COVID-19. Co-authorship and keyword analyses reveal increasing interdisciplinary collaboration and a global research network. The study highlights gaps in research related to cultural differences, digital transformation, and post-pandemic organizational dynamics. It emphasizes the need for future studies to foster cross-disciplinary and international collaborations to advance theoretical frameworks and practical applications. Overall, this bibliometric mapping provides comprehensive insights into the evolution and current state of employee voice research